Abordări subiective şi consensuale ale sărăciei. Despre deprivarea relativă - Voicu, Bogdan (Calitatea Vieții, 2006)
The paper tries to present possible uses of the concept of relative deprivation in assessing poverty and feelings of poverty. A review of the theoretical premises, as well as of the investigation methods, opens the paper. Examples from various measurements across Europe are used to better depict the concept. I argue for the existence of two parameters of relative deprivation: one regards its “subjective” dimension. The other is more “objective”, but its relativeness as to the society standards turns into a measure of consensual poverty. The second part of the paper is devoted to the presentation of the results of various attempts to assess relative deprivation in Romania, starting with the mid 1990s. Finally, I use various data sets to empirically prove the belonging of the concept to the space of subjective and consensual measurement of poverty.